Web-Based Sales Information System Design At Eco Farming Bukit Lawang - Sri Wahyuni br Sembiring; Harry Pratama Figna; Vera Wijaya (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2022)
In Indonesia, internet users reach 150 million people with 56% penetration spread throughout the region. This number is only slightly different from the number of mobile internet users which amounted to 142.8 million people with a penetration percentage of 53%. E-Commerce is a process of buying and selling transactions carried out by buyers and sellers electronically from companies to other companies by utilizing communication and computer networks. At Eco Farming Bukit Lawang has great potential with the existence of excellent natural products, the surrounding community takes advantage of the results. Plants that exist in the Bukit Lawang area, but become in vain because the marketing of information on the results of these plants is not good.